Jewish responses to persecution. Volume 3. 1941-1942 / Jürgen Matthäus ; with Emil Kerenji, Jan Lambertz, and Leah Wolfson ; translators: Norman Bruder [und viele weitere] - Matthäus, Jürgen 1959- Verfasser; Kerenji, Emil Mitwirkender; Lambertz, Jan Mitwirkender; Wolfson, Leah Mitwirkender (Documenting life and destruction, 2013)
Jewish Responses to Persecution: 1941 1942 is the third volume in a five-volume set published in association with the United States Holocaust Memorial Museum that offers a new perspective on Holocaust history. Incorporating historical documents and accessible narrative, this volume sheds light on the personal and public lives of Jews during a period when Hitler s triumph in Europe seemed assured, and the mass murder of millions had begun in earnest. The primary source material presented here, including letters, diary entries, photographs, transcripts of speeches, newspaper articles, and official memos and reports, makes this volume an essential research tool and curriculum companion.